Advances in Immunotherapy for Glioblastoma Multiforme. (19th February 2017) - Huang, Boyuan; Zhang, Hongbo; Gu, Lijuan; Ye, Bainxin; Jian, Zhihong; Stary, Creed; Xiong, Xiaoxing
Abstract : Glioblastoma multiforme (GBM) is the most common primary malignant brain tumor in adults. Patients with GBM have poor outcomes, even with the current gold-standard first-line treatment: maximal safe resection combined with radiotherapy and temozolomide chemotherapy. Accumulating evidence suggests that advances in antigen-specific cancer vaccines and immune checkpoint blockade in other advanced tumors may provide an appealing promise for immunotherapy in glioma. The future of therapy for GBM will likely incorporate a combinatorial, personalized approach, including current conventional treatments, active immunotherapeutics, plus agents targeting immunosuppressive checkpoints.